PENGGUNAAN BAHASA PROKEM DALAM KOMIK KIMI NI TODOKE VOLUME 24 KARYA KARUHO SHIINA - ELSA YUNITA PUTRI; NOVI ANDARI (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2018)
Japanese Jargon which is also known as a wakamono kotoba term is a dynamic language style which will change over time and become a culture in youth daily life in communicating with others. There are many words that are formed from wakamono kotoba. Therefore to make it easier the usage of each word from wakamono kotoba, the words are divided into groups. This study aimed to know the types of wakamono kotoba in Kimi No Todoke comic volume 24. This study used descriptive qualitative method with linguistic approach. The analysis were done by elaborating and analysing types of wakamono kotoba that have been grouped in a descriptive form according to the related theory. The result of the study showed that: from 40 wakamono kotoba that have been found in a data source can be categorized into 7 types, they are: 1) in a form of abbreviation from 2 or more vocabularies; 2) clipping the word; 3) have no change in form both have change in meaning from the original meaning; 4) use the word from katakana ‘go’; 5) use the abbreviated word from katakana ‘go’; 6) combined Japanese language with the word from katakana ‘go’; and 7) there is sound change. Keywords: Linguistics, Language Style, Wakamono Kotoba, Comic